Anaerobic Mesophilic Co-Digestion of Swine Slurry and Hidrolyzate in Batch Reactors: A Case Study - Domingues, Paulo S.; Pala, Helena; Oliveira, Nelson S. (Frontiers in Environmental Science, 2021)
The management of residual flows from swine farms, such as slurry and hydrolyzate, is a serious environmental problem in Portugal, so the search for new solutions is important, especially if they can be implemented in production sites, avoiding the transport of waste. Anaerobic co-digestion can configure a sustainable method of management and valorization of these flows in swine farms, resulting in biogas to produce energy and a digestate with agronomic value. The swine hydrolyzate is the product from the elimination of swine carcasses on the farms, through a hydrolysis process. Its use in the anaerobic process wasn’t found in the literature, identifying the need to evaluate its potential. Thus, anaerobic co-digestion of swine slurry and hydrolyzate was carried out and the main purpose of this research was to find the best feeding ratio between the two substrates in batch test, focusing on biogas production. The study was developed in two phases, both under mesophilic conditions. In the first one, using 100 ml syringes, the effect of the relative proportion of substrates on the anaerobic co-digestion potential was investigated and the effect of pressure sterilization of the substrates on biogas production was verified. In the second phase, a larger scale study was carried out in a 4500 ml digestor, ran under the conditions identified as the most favorable in the preliminary tests. The results obtained allowed us to conclude that the largest volume of accumulated biogas was obtained with the proportion of 90.9% swine slurry : 9.1% swine hydrolyzate (v/v); and that the sterilization of the substrates doesn´t constitute an effective thermal pretreatment. The larger scale test revealed an inefficient anaerobic process due to the inhibitory effect caused by the accumulation of ammonia and volatile organic acids. However, the production yield was 606.8 LBiogas/kgVS and 431.6 LMethane/kgVS, indicating that process allowed a production of biogas and methane higher than the values cited in literature for anaerobic digestion of swine slurry. This result showed that the use of swine hydrolyzate as a co-substrate results in a better balance of nutrients, promoting a better development of microorganisms.